Preliminary Evidence of Apathetic-Like Behavior in Aged Vesicular Monoamine Transporter 2 Deficient Mice - Baumann, Aron; Moreira, Carlos G.; Morawska, Marta M.; Masneuf, Sophie; Baumann, Christian R.; Noain, Daniela (Frontiers in Human Neuroscience, 2016)
Apathy is considered to be a core feature of Parkinson’s disease (PD) and has been associated with a variety of states and symptoms of the disease, such as increased severity of motor symptoms, impaired cognition, executive dysfunction, and dementia. Apart from the high prevalence of apathy in PD, which is estimated to be about 40%, the underlying pathophysiology remains poorly understood and current treatment approaches are unspecific and proved to be only partially effective. In animal models, apathy has been sub-optimally modeled, mostly by means of pharmacological and stress-induced methods, whereby concomitant depressive-like symptoms could not be ruled out. In the context of PD only a few studies on toxin-based models (i.e. 6-OHDA or MPTP) claimed to have determined apathetic symptoms in animals. The assessment of apathetic symptoms in more elaborated and multifaceted genetic animal models of PD could help to understand the pathophysiological development of apathy in PD and eventually advance specific treatments for afflicted patients. Here we report the presence of behavioral signs of apathy in 12 months old mice that express only ~5% of the vesicular monoamine transporter 2 (VMAT2). Apathetic-like behavior in VMAT2 deficient (LO) mice was evidenced by impaired burrowing and nest building skills, and a reduced preference for sweet solution in the saccharin preference test, while the performance in the forced swimming test was normal. Our preliminary results suggest that VMAT2 deficient mice show an apathetic-like phenotype that might be independent of depressive-like symptoms. Therefore VMAT2 LO mice could be a useful tool to study of the pathophysiological substrates of apathy and to test novel treatment strategies for apathy in the context of PD.